PENGARUH PJBL BERBANTUAN METODE WINDOW SHOPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DI SMAN 11 PADANG - Langga Hariani; Anwar, Syafri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
His study aims to analyze the effect of the Project Based Learning (PjBL) model assisted by the window shopping method on students’ learning outcomes in Geography at SMAN 11 Padang. This research employed a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The sample was selected using a cluster random sampling technique, consisting of class XI.F9 as the experimental group (31 students) and class XI.F1 as the control group (31 students). Data were collected through pretest and posttest, reflection questionnaires, and observation questionnaires. Data analysis included descriptive analysis, prerequisite tests (normality test, homogeneity test, and N-gain calculation), and hypothesis testing using an independent sample t-test, as well as supporting qualitative analysis assisted by IBM SPSS version 31. The results showed that the data were normally distributed and homogeneous. The average learning outcomes in the experimental class increased from 51.16 to 82.19. The N-gain value in the experimental class was 72.21% (high category), while in the control class it was 22.56% (low category). The t-test results showed a significance value (Sig. 2-tailed) of < 0.001 (< 0.05), indicating that there was a significant effect of the implementation of the PjBL model assisted by the window shopping method on students’ learning outcomes. In addition, the questionnaire results indicated that most students responded positively to the learning process, as evidenced by increased interest, participation, and learning motivation. Therefore, this learning model is effective in improving students’ learning outcomes in Geography.